Yield and quality decline in vegetatively propagated cultivar tea (Camellia sinensis (l) O. Kuntze) under continuous mechanical harvesting - Taylor, Nicolette Jane (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2016.